Geology and Petrogeochemistry of Lijiapuzi Nb-Ta Granitic Pegmatite Deposit: Implications for Ore Genesis and Prospecting - Jianfei Fu; Yuzeng Yao; Jing Liu; Zining Li; Sanshi Jia; Yemao Pang (Applied Sciences, 2022)
Most of the rare metal pegmatite deposits in China lie in West, Central and South China, and the Lijiapuzi Nb-Ta deposit is the only pegmatite-type Nb-Ta deposit in Northeast China, therefore a detailed study of the Lijiapuzi deposit is of great importance to the metallogeny and exploration of rare metal deposits in Northeast China. The Nb-Ta bearing pegmatites in Lijiapuzi district are composed of a microcline wall zone, a muscovite (lepidolite)-albite intermediate zone and a quartz core, and the rare metal mineralization mainly occurs in the intermediate zone and is intimately related to the albitization. The lithogeochemical features indicate that Lijiapuzi pegmatoids are rich in silicon and alkaline, poor in calcium, magnesium, titanium and phosphorus, and belong to peraluminous granitoid rocks. The enrichment of large ion lithophile elements (LILEs) and depletion of high field-strength elements (HFSEs), the distinct right-inclined REE pattern with obvious Eu negative anomaly, lower ratio of Nb/Ta and higher ratio of La/Nb and Rb/Sr indicate that the pegmatite was of a crustal origin and formed in relatively extensional tectonic setting of post-orogenesis. The pegmatites in Lijiapuzi area can be divided into two categories, i.e., the NW-trending pegmatites are shorter and thicker, with obvious zoning and localized in the upper part of the near-surface, while the NE-trending pegmatites are longer, thinner, devoid of zoning and localized in the lower part of the district. This probably means that excellent ore prospecting potential exists in the lower part of the Lijiapuzi district.